2016
DOI: 10.3390/md14030050
|View full text |Cite
|
Sign up to set email alerts
|

Deep Subseafloor Fungi as an Untapped Reservoir of Amphipathic Antimicrobial Compounds

Abstract: The evolving global threat of antimicrobial resistance requires a deep renewal of the antibiotic arsenal including the isolation and characterization of new drugs. Underexplored marine ecosystems may represent an untapped reservoir of novel bioactive molecules. Deep-sea fungi isolated from a record-depth sediment core of almost 2000 m below the seafloor were investigated for antimicrobial activities. This antimicrobial screening, using 16 microbial targets, revealed 33% of filamentous fungi synthesizing bioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…The marine Sarocladium spp. have also been reported to be active against E. coli (Samuel, Prince, & Prabakaran, ), while S. kiliense , endophytic fungi possessed antibacterial and antifungal properties (Lou et al, ; Navarri et al, ). The genus Penicillium is well known producer of variety of compounds with broad spectrum of biological activity and pharmacological application (Debbab, Aly, Lin, & Proksch, ).…”
Section: Discussionmentioning
confidence: 99%
“…The marine Sarocladium spp. have also been reported to be active against E. coli (Samuel, Prince, & Prabakaran, ), while S. kiliense , endophytic fungi possessed antibacterial and antifungal properties (Lou et al, ; Navarri et al, ). The genus Penicillium is well known producer of variety of compounds with broad spectrum of biological activity and pharmacological application (Debbab, Aly, Lin, & Proksch, ).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistant microorganisms cause killing of about 3 million people each year in the world (Navarri et al, 2016). This threat requires renewal of the traditional antibiotics Underexplored marine environment may represent an untapped reservoir of novel antimicrobial agents (Blunt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Upon using tumour cell line (Caco-2) (Figure 4 C, D), the supernatant of tested compound showed a reasonable degree almost 63.8 % inhibition respectively after 72 h using the MTT assay. On the other hand, using the supernatants of the tested compound showed very low activity towards EI4 (Figure 4 A,B), (HepG2) (Figure 4 E,F) cell line and (MCF-7) (Figure 4 G,H) as detected by MTT assays where they showed only 33 % and 44.6% inhibition respectively after 72 h. Noble et al (2016) reported that secondary metabolites from the marine Pseudoalteromonas sp. inhibited the proliferation of A549 lung carcinoma cells.…”
Section: Thin Layer Chromatographymentioning
confidence: 99%
“…New and complex metabolites from traditional, easy-to-collect natural sources are becoming scarce for intense chemical investigation. Nevertheless, some largely unexplored natural sources, such as endophytes, 23,24 uncultivable or poorly cultivable microorganisms, [25][26][27][28] and marine organisms in extreme growing conditions, 29,30 are attracting more attention from chemists and biologists. In recent years, developments in genomics have revealed that microorganisms have far greater potential to produce new and complex secondary metabolites.…”
Section: Strategies For Diversification Of Natural Productsmentioning
confidence: 99%